2021
DOI: 10.1186/s40359-021-00645-z
|View full text |Cite
|
Sign up to set email alerts
|

Size and shape of plates and size of wine glasses and bottles: impact on self-serving of food and alcohol

Abstract: Background The physical properties of tableware could influence selection and consumption of food and alcohol. There is considerable uncertainty, however, around the potential effects of different sizes and shapes of tableware on how much food and alcohol people self-serve. These studies aimed to estimate the impact of: 1. Plate size and shape on amount of food self-served; 2.Wine glass and bottle size on amount of wine self-poured. Methods 140 adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
2
5
0
Order By: Relevance
“…Consistent with this, larger wine glasses increase purchasing of wine in restaurants, where more wine is sold by the bottle and therefore free-poured by customers and staff into glasses, but not in bars, where more wine is sold by the glass in fixed serving sizes [ 25 ]. Accordingly, one laboratory study found that the larger the glass, the larger the volume of wine that was poured into it [ 49 ]. Additionally, supporting this possible mechanism is evidence suggesting that glass size does not appear to have an effect on micro-drinking behaviours—such as sip size—or perceptions of serving size—when fixed volumes of wine are presented in different sized glasses [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with this, larger wine glasses increase purchasing of wine in restaurants, where more wine is sold by the bottle and therefore free-poured by customers and staff into glasses, but not in bars, where more wine is sold by the glass in fixed serving sizes [ 25 ]. Accordingly, one laboratory study found that the larger the glass, the larger the volume of wine that was poured into it [ 49 ]. Additionally, supporting this possible mechanism is evidence suggesting that glass size does not appear to have an effect on micro-drinking behaviours—such as sip size—or perceptions of serving size—when fixed volumes of wine are presented in different sized glasses [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Twelve out of 15 studies examined the effect of potential moderators, including gender ( n = 8), food preference ( n = 5), prior exposure to diet-related materials ( n = 2), dietary restraint ( n = 2), and serving size labelling ( n = 2). Three studies found that the effects of a smaller single package on reducing consumption or intention to consume was more prominent among males than females [ 40 , 45 ], but five other studies did not observe any difference between genders [ 37 , 41 , 44 , 47 ]. Four studies using popcorn observed the tendency to overeat from a larger package was more prominent when children [ 37 ] and adults [ 42 , 43 ] were offered their preferred snacks (for example, fresh popcorn) compared to not preferred (for example, stale popcorn); however, this was not observed in one study in adults [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…The UK [44] Low Participants intended to consume significantly less (22 g/27%) from the smaller pack than larger pack. This effect was significant for both genders, but it was more prominent for males than for females.…”
Section: Clarke 2020mentioning
confidence: 99%
“…Furthermore, not only proximity to products within supermarkets but also proximity to supermarkets themselves has been identified as a predictor of food consumption and dietary health, which could be a further avenue for designing healthier cities through planning initiatives (Fiechtner et al, 2016). In out-of-home consumption settings such as cafeterias or restaurants, using smaller tableware may reduce serving sizes, so potentially reducing both the amount consumed and the amount of food waste (Clarke et al, 2021).…”
Section: Will the Actions Be Enough?mentioning
confidence: 99%